Grouper cGAS is a negative regulator of STING-mediated interferon response - Zhang, Luhao; Zhang, Xin; Liao, Jiaming; Xu, Linting; Kang, Shaozhu; Chen, Hong; Sun, Mengshi; Wu, Siting; Xu, Zhuqing; Wei, Shina; Qin, Qiwei; Wei, Jingguang (Frontiers in Immunology, 2023)
Cyclic GMP-AMP synthase (cGAS) is one of the classical pattern recognition receptors that recognizes mainly intracytoplasmic DNA. cGAS induces type I IFN responses to the cGAS-STING signaling pathway. To investigate the roles of cGAS-STING signaling pathway in grouper, a cGAS homolog (named EccGAS) was cloned and identified from orange-spotted grouper(Epinephelus coioides). The open reading frame (ORF) of EccGAS is 1695 bp, encodes 575 amino acids, and contains a Mab-21 typical structural domain. EccGAS is homologous to Sebastes umbrosus and humans at 71.8% and 41.49%, respectively. EccGAS mRNA is abundant in the blood, skin, and gills. It is uniformly distributed in the cytoplasm and colocalizes in the endoplasmic reticulum and mitochondria. Silencing of EccGAS inhibited the replication of Singapore grouper iridovirus (SGIV) in grouper spleen (GS) cells and enhanced the expression of interferon-related factors. Furthermore, EccGAS inhibited EcSTING-mediated interferon response and interacted with EcSTING, EcTAK1, EcTBK1, and EcIRF3. These results suggest that EccGAS may be a negative regulator of the cGAS-STING signaling pathway.